Genetic Resources of Livestock and Poultry in Uttarakhand State of India: A Comprehensive Review - , R S Barwal; , Olympica Sarma (Archives of Current Research International, 2025)
Uttarakhand, a northwestern Himalayan state in India, is home to diverse livestock and poultry breeds adapted to its unique agro-climatic conditions. With its rugged terrain and varied ecosystems, the state offers a rich repository of indigenous animal genetic resources. Among these are native cattle like the Badri, goats such as Pantja and Chaugarkha, sheep like Muzzafarnagri, and poultry breeds including Uttara fowl. These animals, well-suited to the challenges of high-altitude living, play a vital role in sustaining rural livelihoods through dairy, meat, wool, egg and manure production. Despite a decline in indigenous livestock populations, grading-up and crossbreeding programmes have instrumental in increasing the production potential of the existing livestock. Notably, while the cattle and buffalo populations have declined, the goat and poultry populations have increased significantly, driven by growing market demands. The review also highlights the critical conservation efforts in the region, including breeding programmes aimed at preserving the genetic diversity of these local breeds. Significant initiatives such as those by the Uttarakhand Livestock Development Board, the Himmotthan Society, and the Department of Animal Genetics & Breeding at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar focus on improving livestock productivity through selective breeding, artificial insemination and advanced reproductive technologies. Furthermore, these efforts aim to integrate modern agricultural practices with the preservation of traditional livestock systems. Genetic characterization of breeds like the Badri cattle, Uttara fowl, and Pantja and Chaugarkha goat breeds has been instrumental in their registration and conservation. The review underscores the importance of maintaining these indigenous genetic resources to ensure the sustainability of the region's agriculture, provide economic stability to farmers, and contribute to India's broader agricultural biodiversity. Continued research and robust policy support are imperative to safeguard these valuable genetic assets for future generations and to harness their full potential in strengthening the nation's livestock sector.